Ferroelectric PLZT thick films grown by poly(1-vinylpyrrolidone-co-vinyl acetate) (PVP/VA)-modified sol–gel process. (March 2016) - Hu, Zhongqiang; Ma, Beihai; Li, Meiya; Koritala, Rachel E.; Balachandran, Uthamalingam
Graphical abstract: Highlights: Ferroelectric thick films were prepared by PVP/VA-modified sol–gel process. Per-coating thickness is 6 times higher than that of conventional sol–gel process. PLZT thick films grown on LNO/Ni exhibited high breakdown strength of 1.6 MV/cm. PVP/VA-modified process is useful for fabricating high power film capacitors. Abstract: We report the growth of ferroelectric Pb0.92 La0.08 Zr0.52 Ti0.48 O3 (PLZT) thick films using a poly(1-vinylpyrrolidone-co-vinyl acetate) (PVP/VA)-modified sol–gel process. A per-coating thickness of ≈0.66 μm has been demonstrated using PVP/VA-modified solution, which is more than doubled that of the PLZT films grown by PVP-modified method, and nearly 6 times the per-coating thickness of films prepared by conventional sol–gel process. PLZT thick films grown on LNO/Ni substrates exhibited denser microstructure, higher remanent polarization (11 μC/cm 2 ) and dielectric tunability (45%), lower leakage current density (≈1.2 × 10 −8 A/cm 2 ), and higher breakdown strength (≈1.6 MV/cm) than those for the samples grown on PtSi substrates. These results demonstrated great potential of using PVP/VA-modified sol–gel process for high power film capacitor applications.